Inventory Optimization in the U.S. Petroleum Industry: Empirical Analysis and Implications for Energy Emergency Policy - Hubbard, R. Glenn; Weiner, Robert J. (Management Science, 1986)
Much of the rapid increases in the price of crude oil during two of the last three supply shocks has been attributed to increased private inventory demand stimulated by the expectation of speculative profits. Government intervention in any future disruption is likely to take the form of releases from the Strategic Petroleum Reserve (SPR). Given that the SPR accounts for but a small fraction of U.S. oil inventories, the reaction of the private sector is critical in evaluating its impact. We incorporate inventory behavior in a model of the world oil market, which is then linked to a short-run macroeconometric model of the U.S. economy. Our model simulations support the view that substantial inventory accumulation accompanies a supply disruption. In the debate over whether the SPR is potentially a potent or impotent resource in an emergency, we lean toward potency. Our model suggests that public releases will not be absorbed in private stockpiles; indeed, their dampening price effects will serve, albeit slightly, to discourage speculative stock build.